2013
DOI: 10.1016/j.hrtlng.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of a telephone coaching program on heart failure home management for family caregivers

Abstract: Objectives To test the feasibility of delivery and evaluate the helpfulness of a coaching heart failure (HF) home management program for family caregivers. Background The few available studies on providing instruction for family caregivers are limited in content for managing HF home care and guidance for program implementation. Method This pilot study employed a mixed methods design. The measures of caregiver burden, confidence, and preparedness were compared at baseline and 3 months post-intervention. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 35 publications
0
58
0
Order By: Relevance
“…Dyads being incongruent reported higher levels of psychosocial distress both within the dyad as individually (28). Another smaller study had similar results; perspectives of dyad members about the future of HF, perceived care needs and end of life issues were found to be congruent at times and incongruent at other times and incongruence was associated with conflicts and distress within dyads (26). Future research is needed to explore the relationship between e.g.…”
Section: Caregiver Experiences; Measurement and Influencing Factorsmentioning
confidence: 83%
See 1 more Smart Citation
“…Dyads being incongruent reported higher levels of psychosocial distress both within the dyad as individually (28). Another smaller study had similar results; perspectives of dyad members about the future of HF, perceived care needs and end of life issues were found to be congruent at times and incongruent at other times and incongruence was associated with conflicts and distress within dyads (26). Future research is needed to explore the relationship between e.g.…”
Section: Caregiver Experiences; Measurement and Influencing Factorsmentioning
confidence: 83%
“…The same research group did a small RCT study showing positive effects in terms of reducing caregiver burden by educational support to caregivers (25). Another pilot study evaluating the effects of a coaching home management program for HF caregivers found that caregiver burden, preparedness and confidence to care improved (26).…”
Section: Caregiver Experiences; Measurement and Influencing Factorsmentioning
confidence: 99%
“…Telecoaching can be used to provide in-home support or advice on risk factor modifications via motivational text messaging (Frederix et al, 2015b) and coaching sessions over the telephone (Piamjariyakul et al, 2013).…”
Section: Telecoachingmentioning
confidence: 99%
“…A pilot study using telemonitoring by an advanced practice nurse after discharge from a hospitalisation due to HF found no effect on emergency department visits, costs, or risk of readmission for patients with HF [88]. There have also been interventions targeting only partners of HF patients [89][90][91][92][93]. Two studies used telehealthcare and phone support, which resulted in reduced caregiver burden and higher stress mastery [89,90].…”
Section: Interventions Targeting Dyads With Heart Failurementioning
confidence: 99%
“…There have also been interventions targeting only partners of HF patients [89][90][91][92][93]. Two studies used telehealthcare and phone support, which resulted in reduced caregiver burden and higher stress mastery [89,90].…”
Section: Interventions Targeting Dyads With Heart Failurementioning
confidence: 99%